Local Aset Analysis in the Cultural Tourism Development of the Sangiran Conservation Area, Central Jawa - Titik Djumiarti; Sri Suwartiningsih; Aldi Herindra Lasso; Titi Susilowati Prabawa (JURNAL ILMU SOSIAL, 2025)
This study explores the sustainability of local communities through the lens of the Sustainable Livelihoods Framework (SLF), focusing on the Sangiran Cultural Heritage Site—a protected area with high tourism potential yet persistent poverty. Using a qualitative case study approach with cross-sectional and comparative analysis, the research investigates how local communities utilize livelihood assets and transform their strategies in response to tourism development. Findings reveal that while natural, human, social, and economic capitals form the basis of community livelihoods, efforts to diversify through cultural and nature-based tourism face constraints. Limited financial literacy, restricted access to financing, and weak internalization of training hinder progress. Sustainable livelihoods depend on innovation, capacity building, strong social networks, and inclusive economic policies. The study highlights the need for future longitudinal research to better understand the dynamic relationship between tourism and community livelihoods.